Subjects in Pazar and Ardesheni Laz - Balkız Öztürk (Dilbilim Araştırmaları Dergisi, 2010)
The aim of this study is to discuss the impact of the loss of case morphology on the structural vs. semantic subject asymmetry in Ardesheni Laz with specific emphasis on verbal agreement morphology associated with subjects. We will show that in comparison to Pazar which still retains its case morphology Ardeshen has acquired different subject agreement patterns to encode the distinction between structural vs. semantic subjects, which in a sense made it become similar to nominative-accusative systems.